The Phenotypic Spectrum of Nephropathies Associated with Mutations in Diacylglycerol Kinase? - Azukaitis, Karolis; Simkova, Eva; Majid, Mohammad Abdul; Galiano, Matthias; Benz, Kerstin; Amann, Kerstin Ute; Bockmeyer, Clemens; Gajjar, Radha; Meyers, Kevin E.; Cheong, Hae Ii; Lange-Sperandio, Baerbel; Jungraithnnayr, Therese; et al. (Journal of the American Society of Nephrology, 2017)
The recent discovery of mutations in the gene encoding diacylglycerol kinase ? (DGKE) identified a novel pathophysiologic mechanism leading to HUS and/or MPGN. We report ten new patients from eight unrelated kindreds with DGKE nephropathy. We combined these cases with all previously published cases to characterize the phenotypic spectrum and outcomes of this new disease entity. Most patients presented with HUS accompanied by proteinuria, whereas a subset of patients exhibited clinical and histologic patterns of MPGN without TMA. We also report the first two patients with clinical and histologic HUS/MPGN overlap. DGKE-HUS typically manifested in the first year of life but was not exclusively limited to infancy, and viral triggers frequently preceded HUS episodes. We observed signs of complement activation in some patients with DGKE-HUS, but the role of complement activation remains unclear. Most patients developed a slowly progressive proteinuric nephropathy: 80% of patients did not have ESRD within 10 years of diagnosis. Many patients experienced HUS remission without specific treatment, and a few patients experienced HUS recurrence despite complete suppression of the complement pathway. Five patients received renal allografts, with no post-transplant recurrence reported. In conclusion, we did not observe a clear genotype-phenotype correlation in patients with DGKE nephropathy, suggesting additional factors mediating phenotypic heterogeneity. Furthermore, the benefits of anti-complement therapy are questionable but renal transplant may be a feasible option in the treatment of patients with this condition.
EVALuna2:25541